The Implementation of Course Review Horay Model Assisted By Question Card Media Toward The Social Study Learning - Lucky, Citra; Setyowati, Dewi Liesnoor; Latiana, Lita (Educational Management, 2020)
This research aimed to examine the differences of the significant-social study learning outcome improvement between the experimental group taught by Course Review Horay assisted by Question Card media and the control group taught by Take and Give learning model assisted by Question Card. This was a Quasi Experimental Designed research. The applied sampling technique was Random Sampling. It was a technique of selecting randomly the sample. It resulted to Kedungwinong 01 Public Primary School with its IV-A class as the experimental group and IV-B class as the control group. The participants consisted of 60 students. The applied data collection technique was a social study learning outcome test. The findings showed differences of the social study learning outcomes for both the experimental group taught by Course Review Horay model assisted by the Question Card media and the control group. It was shown by the N-Gain score of the experimental group, 63.9. Meanwhile, the control group’s N-Gain score was 52.3. This finding was supported by the independent sample t-test showing that sig of (2-tailed) is 0.024<0.05. The social study learning outcomes of the group taught by Course Review Horay assisted by the Question Card are higher. The implementation of Course Review Horay assisted by the Question Card could be applied as an alternative for the teachers to improve the students' social study learning outcomes.